2019
DOI: 10.7759/cureus.4756
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Hazards of X-Ray Imaging and Perception Regarding Necessary Safety Measures to be Taken During X-Ray Imaging Procedures Among Patients in Public Sector Tertiary Hospitals of Karachi, Pakistan

Abstract: Background X-ray imaging is a common procedure performed on a regular basis for diagnostic purposes all over the world. The use of X-rays is increasing rapidly with the introduction of new radiation-oriented therapeutic practices. Although it carries significant diagnostic benefits, extensive exposure to X-ray imaging has been shown to be associated with multiple dose-dependent health risks. Awareness and knowledge among patients regarding the effects of X-ray imaging, therefore, becomes important. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Even though higher incidence and lower survival rates are observed in the less educated, they are unaware of this reality [29]. However, this finding follows a study by Naqvi et al who reported a greater awareness of radiation exposure with a higher level of education [30].…”
Section: Jhrsupporting
confidence: 60%
“…Even though higher incidence and lower survival rates are observed in the less educated, they are unaware of this reality [29]. However, this finding follows a study by Naqvi et al who reported a greater awareness of radiation exposure with a higher level of education [30].…”
Section: Jhrsupporting
confidence: 60%
“…Since a single radiation-damaged cell can affect other cells in a person, radiation has the greatest detrimental effect on single cells. All people have lifetime exposure to both high and low levels of radiation, which is harmful [5]. One major ambient crisis is radiation pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Translating this concept to radiology, it becomes important to understand the knowledge that users have regarding this topic. Mainly because it is an area that, over the years, has grown in terms of equipment, examination protocols, and clinical indications, which has led to an increase in the number of people exposed to ionizing radiation [5,10,11]. Health literacy in radiology and understanding the risks associated with ionizing radiation are important for women of childbearing age, particularly because they may require medical imaging procedures that involve exposure to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy in radiology and understanding the risks associated with ionizing radiation are important for women of childbearing age, particularly because they may require medical imaging procedures that involve exposure to radiation. Frequently, they do not have enough information to ensure the needed X-ray protection [5,[11][12][13][14][15][16]. While the risks of radiation from medical imaging are generally low for adults, it is still important to understand the potential effects on the developing fetus [17,18].…”
Section: Introductionmentioning
confidence: 99%